Thank You to Our 2018 Peer Reviewers. Issue 21 (6th November 2019) - Rajaram, Harihar; Diffenbaugh, Noah; Camargo, Suzana; Cardenas, M. Bayani; Carey, Rebecca; Cobb, Kim; Cory, Rose; Cronin, Meghan; Dombard, Andrew; Donohue, Kathleen; Flesch, Lucy; Giannini, Alessandra; et al.
Abstract: On behalf of the journal, AGU, and the scientific community, the Editors would like to sincerely thank those who reviewed manuscripts for Geophysical Research Letters in 2018. The hours reading and commenting on manuscripts not only improves the manuscripts but also increases the scientific rigor of future research in the field. We particularly appreciate the timely reviews, in light of the demands imposed by the rapid review process at Geophysical Research Letters . With the revival of the "major revisions" decisions, we appreciate the reviewers' efforts on multiple versions of some manuscripts. Many of those listed below went beyond and reviewed three or more manuscripts for our journal, and those are indicated in italics. In total, 4, 484 referees contributed to 7, 557 individual reviews in journal. Thank you again. We look forward to the coming year of exciting advances in the field and communicating those advances to our community and to the broader public. Key Point: In total, 4, 484 referees contributed to 7, 557 individual reviews in journal